TERDAPAT HUBUNGAN ANTARA KOMUNIKASI TERAPEUTIK PERAWAT DENGAN TINGKAT KECEMASAN PASIEN PRE OPERASI APPENDECTOMY - Miptahul Ridwan; Sri Arini Winarti Rinawati; Deby Zulkarnain Rahadian Syah (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Anxiety is a n unpleasant emotional, characterized by fear and tense physical symptoms as respond of stress. Anxiety commonly happens to pre-operative patients. Therapeutic communication is one of the modality therapies to anxious patients. Therapeutic communication is a communication which facilitates recovery to patients by giving safe and comfortable feelings and promotes trusts between health care providers and patients. Objective: To investigate the correlation between the patients perception to the nurses therapeutic communication and the anxiety level of appendictomy pre-operative patients in Yogyakarta Hospital and Hardjolukito Hospital. Methodology: This research was an analytic survey with cross-sectional design. Twenty-three respondents were involved as samples by consecutive sampling technique. Statistical test used in this research is non- parametric and spearman rank. Results: There was a correlation between patients perception to the nurse therapeutic communication and t h e anxiety level on appendictomy pre-operative patients. Non-parametric test used Spearmen rank rho formula showed a significant result of p-value= 0.014 p<0.05, with correlation coefficient of 0.506. Conclusion: There was a significant correlation between patients perception to the nurse therapeutic communication with the anxiety level of appendictomy pre-operative patients. Keywords: Perception, Therapeutic Communication, Anxiety Level